LAND REFORM AND SUSTAINABLE DEVELOPMENT - A MARRIAGE OF NECESSITY - Juanita M Pienaar, (Obiter, 2022)
In order for land reform to be successful in the agricultural arena, the end-result must promote sustainable development. The question is whether legislation and policy initiatives have been conducive in furthering the partnership between land reform and sustainable development. Although the link between the two seems apparent, after a brief analysis of existing land reform legislation it is clear that legislation generally does not reflect this. Many actors have an impact on the harmonization of land reform and sustainable development, inter alia (a) problems resulting from the former racially-based land control approach and (b) geographical and climatic factors. The problems experienced in the rural areas in especially the former national states and self-governing territories are discussed in more detail. In order to place the current situation in perspective, recent developments that impact on land reform and development are then discussed, namely the Land Redistribution for Agricultural Development Plan and the Strategic Plan for SA Agriculture. In light of these developments various shortcomings are further identified that still hamper the closer working partnership between land reform and sustainable development. The conclusion is reached that the mere transfer of land is no guarantee for a successful land reform programme. What is needed, is a balanced approach towards addressing the demand for land on the one hand and maintaining agricultural production on the other.